VORTEX CONVERTER OF CONTINUOUS MEDIUM FLOW - Serebryakov, R. (Energy and Automation, 2016)
The problems of conversion of solar and wind energy, as well as the use of hydro energy laminated swirling flows can play an important role in connection with the thermal-hydraulic feature of these trends, concentrating in the swirl jet flows kinetic energy scattered in the surrounding area. This allows the use of low-potential thermal ascending flow induced by solar heating, weak wind and kinetic energy flows in rivers and water channels.